Effectiveness of Health Risks of Cigarette Smoking Education-based Information-Motivation-Behavioral Skill Model of Increasing Smoking Cessation Motivation - Rivan Virlando Suryadinata; Amelia Lorensia; Rizki Hersandio (UPT Publikasi Ilmiah Universitas Islam Bandung, 2025)
Smoking is responsible for a high proportion of morbidity and mortality in Indonesia. Because of the loss in terms of health and economy, the smoking cessation program is the main treatment option for smokers. The information-motivation-behavioral skill (IMB) explains that knowledge is not the only determinant of behavior change, but also the motivation and behavioral skills of individuals. The purpose of the study was to develop a health education strategy by exploring the conditions of knowledge that could affect motivation to quit smoking. This research employed interpretive phenomenological analysis (IPA) on male young active smokers as students in Surabaya, East Java, from April to July 2021. The collection of samples employed snowball and purposive sampling, utilizing the in-depth interview method until data saturation was achieved. The data analysis process involved coding and verbatim transcription of the interview results, which described the interview process and provided research reflection on the interview results (self-reflection). The study was conducted on 23 students. Most respondents fell within the 20–23-year age range. On the topic of the dangers of cigarettes, they showed they only knew that they were dangerous, but didn't know to what extent nicotine and tar were hazardous to health. On the dangers of smoking to health topic, respondents knew the impact of tobacco on health, but didn't care about the effects on health. In conclusion, the level of knowledge related to smoking cessation can inform therapeutic options tailored to individual conditions.